Chemistry teaching efficacy, student conceptual understanding, process skills and attitude - Mata, Amaya B. (2005)
This study aimed to determine if chemistry teaching efficacy is related to teacher characteristics and student learning outcomes and to identify factors that contribute to efficient chemistry teaching. Data were collected from thirty chemistry teachers and 790 third year high school students from 16 secondary schools in Albay. Various tests and scales were used to gather data. Results showed that majority of the teachers do not have a specialization on chemistry but have very favorable attitudes and high aptitudes in teaching chemistry. Teachers attribute their efficacy to content knowledge, teaching experience, modeling of expert teachers, in-service trainings, nature of students, resources, administrative and collegial support, and parents' support. However, student performance is not reflective of teacher efficacy in teaching chemistry.
Thesis (M.A. Chemistry Education)--University of the Philippines, Diliman.
Keywords: Chemistry -- Study and teaching (Secondary) -- Philippines -- Albay; High school students -- Philippines -- Albay -- Attitudes; Effective teaching -- Philippines -- Albay